Multi-pathway human exposure assessment of phthalate esters and DINCH. (March 2018) - Giovanoulis, Georgios; Bui, Thuy; Xu, Fuchao; Papadopoulou, Eleni; Padilla-Sanchez, Juan A.; Covaci, Adrian; Haug, Line S.; Cousins, Anna Palm; Magnér, Jörgen; Cousins, Ian T.; de Wit, Cynthia A.
Abstract: Phthalate esters are substances mainly used as plasticizers in various applications. Some have been restricted and phased out due to their adverse health effects and ubiquitous presence, leading to the introduction of alternative plasticizers, such as DINCH. Using a comprehensive dataset from a Norwegian study population, human exposure to DMP, DEP, DnBP, DiBP, BBzP, DEHP, DINP, DIDP, DPHP and DINCH was assessed by measuring their presence in external exposure media, allowing an estimation of the total intake, as well as the relative importance of different uptake pathways. Intake via different uptake routes, in particular inhalation, dermal absorption, and oral uptake was estimated and total intake based on all uptake pathways was compared to the calculated intake from biomonitoring data. Hand wipe results were used to determine dermal uptake and compared to other exposure sources such as air, dust and personal care products. Results showed that the calculated total intakes were similar, but slightly higher than those based on biomonitoring methods by 1.1 to 3 times (median), indicating a good understanding of important uptake pathways. The relative importance of different uptake pathways was comparable to other studies, where inhalation was important for lower molecular weight phthalates, and negligible for the higher molecular weight phthalates and DINCH. Dietary intake was the predominant exposure route for all analyzed substances. Dermal uptake based on hand wipes was much lower (median up to 2000 times) than the total dermal uptake via air, dust and personal care products. Still, dermal uptake is not a well-studied exposure pathway and several research gaps (e.g. absorption fractions) remain. Based on calculated intakes, the exposure for the Norwegian participants to the phthalates and DINCH was lower than health based limit values. Nevertheless, exposure to alternative plasticizers, such as DPHP and DINCH, is expected to increase in the future and continuous monitoring is required. Highlights: Diet is the major route of human exposure to phthalates and DINCH. Human risk related to phthalates and DINCH is low for the adult study population. Indoor environmental concentrations can be successfully linked to human body burden. Dermal uptake of phthalates needs further investigation.